Carbon‐Carbon and Carbon‐Heteroatom Bond Formation Reactions Using Unsaturated Carbon Compounds. Issue 2 (1st October 2018) - Sultan, Shaista; Shah, Bhahwal Ali
Abstract: The carbon‐carbon and carbon‐heteroatom bond formation reactions are considered as a fundamental tool in synthetic organic chemistry. They have been effectively utilized in the synthesis of medicinally significant molecules, agrochemicals and valuable compounds in material sciences. This has been primarily enabled by highly efficient protocols arising from divergent mechanistic pathways. In this personal account, we aim to discuss some recent advances in carbon‐carbon or carbon‐heteroatom bond formation reactions to which our group has actively contributed. More specifically, this record focuses on the use of unsaturated carbon compounds for the construction of C−C and C−X bonds. Abstract : The reactivity of alkenes, alkynes and carbonyl compounds is central to a majority of carbon‐carbon and carbon‐heteroatom bond formation reactions. This account details the progress of our group in exploring reactivity of unsaturated compounds for the construction of C−C and C−X bonds.